1990
DOI: 10.2527/1990.6861505x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of breed, parity, day of lactation and number of kits on milk production of rabbits.

Abstract: Lactation records (n = 86) from 60 does of four breeds (Californian, New Zealand White, Palomino and White Satin) were analyzed to assess the effects of breed, parity, day of lactation and number of kits on milk production. Breed of doe tended (P less than .07) to be important for mean milk yield according to ANOVA results. Californian does had numerically higher production than did does of the other breeds. Doe body weight, litter size born alive and weaned and litter weaning weight, likewise, were not influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 0 publications
2
37
1
1
Order By: Relevance
“…At slaughter (on day 35 post-partum) the body condition of females was similar in both groups, except 524 production by the doe and an increase of milk availability for suckling young. This is in agreement with Lebas [13,14] and McNitt and Lukefahr [17] who showed that milk production increases with the number of suckling rabbits, but individual milk intake decreases. On days 16 and 25 of lactation, 8.9% and 7.4% of the rabbits from litters of 10 young ingested less than 5 g of milk.…”
Section: Feed Intake and Performance Of Femalessupporting
confidence: 90%
“…At slaughter (on day 35 post-partum) the body condition of females was similar in both groups, except 524 production by the doe and an increase of milk availability for suckling young. This is in agreement with Lebas [13,14] and McNitt and Lukefahr [17] who showed that milk production increases with the number of suckling rabbits, but individual milk intake decreases. On days 16 and 25 of lactation, 8.9% and 7.4% of the rabbits from litters of 10 young ingested less than 5 g of milk.…”
Section: Feed Intake and Performance Of Femalessupporting
confidence: 90%
“…Lukefahr et al (1983) demonstrated that New Zealand White does are superior (+ 30%) to Californian does and that crossbred rabbits of both breeds are superior than the pure breeds. However, in another study, the same team determined a comparable milk production for the 4 breeds tested (Calfornian, New Zealand White, Palomino and White Satin) (McNitt and Lukefahr, 1990), which indicate that the genetic background of the particular populations is perhaps more important than the breed itself.…”
Section: Genotypementioning
confidence: 99%
“…McNitt and Lukefahr (1990) reported even an increase till the 7 th litter; however because less productive females were progressively culled out, their selection policy has favoured the milk yield with increasing parity order. The highest difference is found between the 1 st and 2 nd lactation.…”
Section: Parity Ordermentioning
confidence: 99%
See 1 more Smart Citation
“…Sedki et al (2002) reported that the effect of parity on kit weight at weaning was significant (P<0.05 or 0.01). An increment of milk production with the parity order has been reported (McNitt and Lukefahr, 1990;Hassan et al, 1992) that could be correlated to the development of the mammary glands.…”
Section: Paritymentioning
confidence: 94%